(i) To verify,
cos A cos Bsin(A + B)=tan A + tan B.
Substituting value of A and B in L.H.S. of the equation, we get :
⇒cos A cos Bsin(A + B)⇒cos 60° cos 30°sin(60° + 30°)⇒21×23sin 90°⇒431⇒34.
Substituting value of A and B in R.H.S. of the equation, we get :
⇒tan A + tan B⇒tan 60° + tan 30°⇒3+31⇒33+1⇒34.
Since, L.H.S. = R.H.S.
Hence, proved that cos A cos Bsin(A + B)=tan A + tan B.
(ii) To verify,
sin A sin Bsin(A - B)=cot B - cot A
Substituting value of A and B in L.H.S. of the equation, we get :
⇒sin A sin Bsin(A - B)⇒sin 60° sin 30°sin(60° - 30°)⇒sin 60° sin 30°sin 30°⇒23×2121⇒4321⇒234⇒32.
Substituting value of A and B in R.H.S. of the equation, we get :
⇒ cot B - cot A
⇒ cot 30° - cot 60°
⇒ 3−31=33−1
⇒ 32.
Since, L.H.S. = R.H.S.
Hence, proved that sin A sin Bsin(A - B)=cot B - cot A.